2008
DOI: 10.1002/bsl.794
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional MRI‐ findings in children and adolescents with antisocial behavior

Abstract: We describe the developmental taxonomy of children with CD and focus on those with the early onset subtype. Structural MRI data of these children and antisocial adults are recapitulated. The impact of investigating neurobiological underpinnings of antisocial behavior and how this might contribute to future forensic and psychiatric assessments is discussed. RESULTS/ CONCLUSION: Children display similar structural aberrations of fronto-limbic structures to adults with antisocial behavior, and amygdala dysfunctio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 64 publications
3
22
0
Order By: Relevance
“…Moreover, only a small number of the participants in this study had received a CD diagnosis. However, 18% of the sample was diagnosed with CD, which is about twice the rate of lifetime CD prevalence in the general population (∼10%, Vloet et al , 2008). This might result from the fact that the present sample is enriched with participants characterized by psychosocial and obstetric risk factors.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, only a small number of the participants in this study had received a CD diagnosis. However, 18% of the sample was diagnosed with CD, which is about twice the rate of lifetime CD prevalence in the general population (∼10%, Vloet et al , 2008). This might result from the fact that the present sample is enriched with participants characterized by psychosocial and obstetric risk factors.…”
Section: Discussionmentioning
confidence: 92%
“…While this restricts the generalizability of the findings in light of evidence suggesting that half of ASPD patients had a history of CD, it is also notable that only 25–30% of CD patients later develop ASPD (for review see Vloet et al , 2008). However, the absence of a current diagnosis does not necessarily imply that individuals in this study qualitatively differ from those who develop ASPD, as brain activity may be a state-independent vulnerability marker.…”
Section: Discussionmentioning
confidence: 98%
“…We also hypothesized that cerebellum and basal ganglia deficits would be found in the ADHD group. The lack of previous evidence implicating white matter in antisocial groups 9,47,48 and mixed evidence in patients with ADHD 8 prevented detailed hypotheses for group white matter differences, but we expected ADHD-specific corpus callosum deficits, as indicated by meta-analytic review. 2 A secondary aim was to determine if conduct disorder or ADHD symptom severity was linearly associated with any abnormal volumetric finding.…”
Section: Introductionmentioning
confidence: 90%
“…Although results vary somewhat across antisocial disorder studies of different age groups, there is consistent evidence for reduced grey matter volume in the temporal lobe, including lateral and medial (e.g., amygdala, hippocampus) regions, in patients with conduct disorder. 9 Meta-analyses have shown that brain volume deficits in patients with ADHD are consistently found in the cerebellum, the corpus callosum splenium, total brain volume, right cerebral volume and right caudate. 2 Many brain structure studies report evidence of frontal lobe volume reductions in samples of youth with primary diagnoses of either conduct disorder 5 or ADHD, 8 but studies vary in their specific findings.…”
Section: Introductionmentioning
confidence: 99%
“…The span of forensic psychiatry will likely develop in two areas; trial consultant and juror consultant. The field of forensic psychiatry can benefit greatly from advanced technology, e.g., neuroimaging, MRI of brain (Vloet et al, 2008). It has been shown that dysfunction of frontal cortex and limbic system is associated with antisocial behavior such as criminal and violent behavior (Vloet et al, 2008).…”
mentioning
confidence: 99%